Long-Term Outcome Following Concomitant Surgical Ablation for Atrial Fibrillation at University Hospital Basel: A Retrospective Study - Hersperger, Elodie; Schaerli, Nicolas; Gahl, Brigitta; Reuthebuch, Oliver; Eckstein, Friedrich S.; Winkler, Bernhard; Grapow, Martin T. R. (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: This study aims to examine the success of concomitant surgical ablation in patients with atrial fibrillation after one, three, and five years. Additionally, important predictors for rhythm outcome and rates of permanent pacemaker implantations were analyzed. Materials and Methods: In this retrospective study, we included patients who were referred to the University Hospital of Basel, Switzerland, between 2011 and 2017. Primary outcome was one-year success of surgical ablation. Secondary outcomes include heart rhythm during entire follow-up, three- and five-years success, and need for additional arrhythmia interventions (incl. pacemaker implantation). Results: A total of 120 patients were analyzed and divided into two groups: pulmonary vein isolation (n = 55) and left atrial (n = 65). The median follow-up time was 4.4 years. Sinus rhythm was present in 66%, 64%, and 67% after one, three, and five years, respectively. When adjusted for preoperative type of atrial fibrillation, left atrial lesion set increased the chance of achieving sinus rhythm within 5 years by factor 6.5. The pacemaker-implantation rate was 22%, with significantly more pacemaker implantations in the left atrial group (9% vs. 32%, p = 0.0043). Conclusions: These real-world data demonstrate the high success rate of concomitant surgical ablation for atrial fibrillation. Our study highlights the importance of preoperative discussion in an interdisciplinary heart team to weigh the effectiveness of surgical ablation against the risk of a pacemaker implantation.